The #1 lawyer - Patterson, James, 1947-; Allen, Nancy (Lawyer) (Little, Brown & Company, 2024)
A small-town lawyer with a big-time reputation, Stafford Lee Penney, Mississippi's #1 lawyer who has never lost a case, when his wife is scandalously killed, spirals into a legal and personal legal streak, ruining his career, and making him the nation's #1 suspect.